Pseudo altitude: A new perspective on the auroral density cavity. Issue 7 (24th July 2013) - Alm, L.; Marklund, G. T.; Karlsson, T.; Masson, A.
Abstract : [1] Studying the density distribution inside the auroral density cavity is complicated by the difficulties in achieving simultaneous measurements within the same flux tube at different altitudes. Comparisons between different events are complicated by variations in both the location of the density cavity and the location of the related potential structure. Describing the spacecraft's location inside the density cavity relative to the potential structure instead of the Earth offers a more practical and consistent frame of reference, a pseudo altitude. The pseudo altitude is determined by comparing the potential drop above the spacecraft, as determined from the characteristic energy of the downward electrons, with the parallel potential drop below the spacecraft, determined from the characteristic energy of the upward ions. A pseudo altitude of 0 corresponds to the bottom of the potential structure and a pseudo altitude of 1 to the top of the structure. Seven events from 2008 were selected, each of which corresponds to a Cluster crossing of a mainly quasi‐static potential structure. All of the events exhibit a consistent anticorrelation between the pseudo altitude and the electron density. No upper limit of the density cavity can be observed, while all cavities have a lower limit above a pseudo altitude of 0.33. These observations show that the auroral density cavity is predominately concentrated to the upper parts of the quasi‐static potential structure. Key Points: Using pseudo altitude facilitates comparisons between different events The lower limit of the density cavity is located above a pseudo altitude of 0.33 No upper limit of the density cavity is found